Bortezomib Induced Hepatitis B Reactivation. (30th April 2014) - Hussain, Salwa; Jhaj, Ruby; Ahsan, Samira; Ahsan, Muhammad; Bloom, Robert E.; Jafri, Syed-Mohammed R.
Abstract : Background . It has recently been reported that hepatitis B (HBV) reactivation often occurs after the use of rituximab and stem cell transplantation in patients with lymphoma who are hepatitis B surface antigen (HBsAg) negative. However, clinical data on HBV reactivation in multiple myeloma (MM) is limited to only a few reported cases. Bortezomib and lenalidomide have remarkable activity in MM with manageable toxicity profiles, but reactivation of viral infections may emerge as a problem. We present a case of MM that developed HBV reactivation after bortezomib and lenalidomide therapy. Case Report . A 73-year-old female with a history of marginal cell lymphoma was monitored without requiring therapy. In 2009, she developed MM, presenting as a plasmacytoma requiring vertebral decompression and focal radiation. While receiving radiation she developed renal failure and was started on bortezomib and liposomal doxorubicin. After a transient response to 5 cycles, treatment was switched to lenalidomide. Preceding therapy initiation, her serology indicated resolved infection. Serial monitoring for HBV displayed seroconversion one month after change in therapy. Conclusion . Bortezomib associated late HBV reactivation appears to be a unique event that requires further confirmation and brings to discussion whether hepatitis B core positive individuals would benefit from monitoring of HBV activation while on therapy.